2019
DOI: 10.1172/jci96313
|View full text |Cite
|
Sign up to set email alerts
|

Spatially distinct tumor immune microenvironments stratify triple-negative breast cancers

Abstract: Understanding the tumor immune microenvironment (TIME) promises to be key for optimal cancer therapy, especially in triple-negative breast cancer (TNBC). Integrating spatial resolution of immune cells with laser capture microdissection gene expression profiles, we defined distinct TIME stratification in TNBC, with implications for current therapies including immune checkpoint blockade. TNBCs with an immunoreactive microenvironment exhibited tumoral infiltration of granzyme B + CD8 + T cells (GzmB + CD8 + T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
302
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(343 citation statements)
references
References 56 publications
13
302
2
Order By: Relevance
“…These discrepancies suggest that when considered alone, molecular subtypes or immune infiltration does not fully capture the varied clinical course of pGBMs. Our work established that both factors have independent prognostic value and combining them significantly improved our ability to predict survival, as also reported by others (Gruosso et al , 2019; Zeng et al , 2019), including recently in GBM (Klopfenstein et al , 2019).…”
Section: Discussionsupporting
confidence: 88%
“…These discrepancies suggest that when considered alone, molecular subtypes or immune infiltration does not fully capture the varied clinical course of pGBMs. Our work established that both factors have independent prognostic value and combining them significantly improved our ability to predict survival, as also reported by others (Gruosso et al , 2019; Zeng et al , 2019), including recently in GBM (Klopfenstein et al , 2019).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, accumulating evidence suggests that the density of stroma‐infiltrating immune cells reflects the focal immune response of patients to chemotherapy regimens and may serve as a promising predictor 11‐13 . Although some studies have investigated the prognostic relevance of some immune cells in TNBC, there are few systematic studies on the association between the overall stromal immune cell signature and clinical outcomes 12,14,15 …”
Section: Introductionmentioning
confidence: 99%
“…2c ). To gain insight into the cellular sources of LOX and LH2 in human tumors, we used laser capture microdissection to isolate regions of tumor epithelium and stroma to identify the origins of LOX and LH2 in invasive human breast cancers (38, 39). Gene expression analysis of stromal and epithelial compartments revealed that the stromal cells in the tumor tissue expressed significantly more LOX and PLOD2 than the associated tumor epithelium.…”
Section: Resultsmentioning
confidence: 99%